The Long run impact of technical and vocational education and training in Pakistan - KHAN, Qaisar (KDI School, 2016)
Human capital is considered as one of the most important determinants of economic growth in recent years due to rapid technological change, globalization and economic liberalization. These rapid changes have prompted the Government of Pakistan like other developing countries, to prioritize skills development as a key strategy for economic growth. This study explores the long run relationship between technical and vocational education and economic growth in Pakistan by using autoregressive distributed lag (ARDL) framework. The estimated coefficient shows that technical and vocational education has a positive and significant impact on economic growth in the long run and can play big role in boosting economy by creating skilled and demand driven individuals in labor market. I also suggested that the government should invest more on technical and vocational education to produce strong human base that can further strengthen labor market with productive workforce and can change the status of Millennium Development Goals (MDGs).
Thesis(Master) --KDI School:Master of Development Policy,2016